Implementation of the special program in the arts curriculum in a public secondary school - Leocario, Ryan Estacio; Pawilen, Greg Tabios (2015)
Access online through this link: https://journals.upd.edu.ph/index.php/ali/article/view/4545
Keywords: Arts education; Curriculum implementation; Secondary education